The Polish wage inequality explosion - Newell, Andrew; Socha, Mieczyslaw W. (Bonn, 2007)
"This paper presents and analyses the sharp increase in hourly wage inequality after 1998 in Poland. The increase was similar in magnitude to the much-studied increase in British wage inequality during the 1980s. Using data from the Polish Labour Force Survey, we find this increase to be associated with rising wage differentials and within-group variances at both the upper and lower ends of the wage distribution. These increases are associated with differences in wage-setting patterns between the public and private sector as well in the rapid increase in the demand for educated labour. One important difference between the sectors is the lack of an impact of local labour market conditions, or wage curve, clearly evident in private sector wages, on public sector wages."